STRATEGI PENINGKATAN KEPATUHAN WAJIB PAJAK DALAM PELAPORAN SURAT PEMBERITAHUAN (SPT) TAHUNAN DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA SEMARANG CANDISARI - Pradini, Agriani Junita; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2018)
Taxes are a source of major domestic acceptance. Low levels of compliance in the reporting annual informing letter ln Kantor Pelayanan Pajak (KPP) Pratama Semarang Candisari This is caused by the low level of awareness of the tax payers as well as suboptimal functioning of existing facilities and infrastructure. The purpose of this study is to formulate a strategy to increase Taxpayer compliance in annual informing letter in Kantor Pelayanan Pajak (KPP) Pratama. The research method used is descriptive qualitative approach with data collection techniques interviews, observation, and study of the literature. SWOT analysis techniques and Litmus Test is used to produce eight strategic issues.. The strategy that has the highest score i.e. increase effort of socialization about reporting annual informing letter by leveraging the positive response of Taxpayers toward the socialization as well as enforcement of the regulations. Recommendations to improve Taxpayer compliance, needs to be improved through various efforts such as improving the socialization of reporting annual informing letter periodic and ongoing as well as carry out missions build trust and awareness of Taxpayers through the enforcement of taxation applies.